2005
DOI: 10.1007/s10517-005-0251-0
|View full text |Cite
|
Sign up to set email alerts
|

Human Fetal Neural Stem Cells in Rat Brain: Effects of Preculturing and Transplantation

Abstract: The fate of human fetal stem/progenitor cells transplanted into rat brain depends on conditions of preculturing (long or short) and state and site of transplantation. Human nestin-positive stem cells cultured according to the short protocol did not migrate into hypoxic and normal brain after transplantation, but actively migrated in damaged spinal cord. After transplantation of long-cultured cells into the brain mainly committed neuroblasts and solitary nestin-positive cells migrated from the site of transplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…[10][11][12] Experimental studies in rat models have demonstrated the potential efficacy of fetal stem cells in treating liver diseases, kidney diseases, and diseases of the central nervous system. [13][14][15][16][17] The therapeutic effects of fetal stem cell may be related directly to embryo-specific growth factors, cytokines, and other signaling molecules that are able to activate recovery and survival in the recipient's own cells. 11 It is believed that introducing suspensions of fetal cells into the patient using network signaling can activate specialized and progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Experimental studies in rat models have demonstrated the potential efficacy of fetal stem cells in treating liver diseases, kidney diseases, and diseases of the central nervous system. [13][14][15][16][17] The therapeutic effects of fetal stem cell may be related directly to embryo-specific growth factors, cytokines, and other signaling molecules that are able to activate recovery and survival in the recipient's own cells. 11 It is believed that introducing suspensions of fetal cells into the patient using network signaling can activate specialized and progenitor cells.…”
Section: Discussionmentioning
confidence: 99%